(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Stakeholder safety plays a pivotal role in the growth of any industry, particularly in the manufacturing industry. Thus, firms have realised their obligation towards stakeholder safety. Objectives: While past studies have highlighted the role of social media strategic capabilities (SMSC) in promoting stakeholder safety performance (SSP), this study examines the direct impact of SMSC on SSP and the mediating effect of firm reputation (FR) and circular economy entrepreneurship (CEE) in the SMSC-SSP relationship. Methods: This study collected 152 responses from small and medium manufacturing enterprises in Nepal via an online survey. The study used the partial least square structural equation modelling (PLS-SEM) technique for data analysis and interpretations. Results: This study reveals that while SMSC has no direct and significant influence on SSP, its indirect effects on SSP via FR and CEE significantly indicate full mediation effects. These findings demonstrate that social media platforms are excellent sources of information for firms in building strong stakeholder collaborations, amassing other external resources, boosting FR, and aiding in the exploitation of CE opportunities. Conclusions: Drawing on stakeholder theory and resource-based view, this study is among the first to develop SMSC, firm reputation, and circular economy entrepreneurship as antecedents for achieving SSP in the context of an emerging economy. Manufacturing firms’ managers may promote SSP by identifying new safety approaches via information derived from social media platforms, which boosts reputation and circular economy entrepreneurship. Keywords: Social media strategic capability; Stakeholder safety performance; Firm reputation; Circular economy entrepreneurship; Manufacturing firms